2023
DOI: 10.21926/cr.2303020
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Photocatalytic Application Towards Wastewater Treatment

Abstract: With increasing population levels and rapidly growing industries worldwide, the purification of water contaminated with different impurities is one of the biggest challenges we face in recent times. Photocatalysis holds great potential as an efficient mineralization process to remove the foreign matter present in wastewater. Rapid advancement in innovative materials development has made photocatalysis the frontrunner among different water treatment methods. Our main priority lies in different strategic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Investigating metal-oxide-based semiconductors, including TiO 2 , SnO 2 , CeO 2 , ZrO 2 , WO 3 , and ZnO, researchers aim to leverage these photocatalysts in degrading organic pollutants within wastewater. 93,94 In their 2023 study, Mei et al investigated the challenges still preventing the widespread use of photocatalytic wastewater treatment technology in industries. They found that even though scientists have been working on photocatalysis for over three decades it is still not widely used because of various challenges.…”
Section: Effect Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigating metal-oxide-based semiconductors, including TiO 2 , SnO 2 , CeO 2 , ZrO 2 , WO 3 , and ZnO, researchers aim to leverage these photocatalysts in degrading organic pollutants within wastewater. 93,94 In their 2023 study, Mei et al investigated the challenges still preventing the widespread use of photocatalytic wastewater treatment technology in industries. They found that even though scientists have been working on photocatalysis for over three decades it is still not widely used because of various challenges.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The primary emphasis is on enhancing photocatalytic efficiency and devising economically viable approaches that are tailored for industrial use. Investigating metal-oxide-based semiconductors, including TiO 2 , SnO 2 , CeO 2 , ZrO 2 , WO 3 , and ZnO, researchers aim to leverage these photocatalysts in degrading organic pollutants within wastewater. , …”
Section: Parameters Affecting the Photocatalytic Dye Degradationmentioning
confidence: 99%
See 1 more Smart Citation